URGENSI USHUL FIQIH TERHADAP DINAMIKA KEHIDUPAN MASYARAKAT - Ummi Kulsum; Siti Aisyah (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2024)
Abstract Ushul fiqh is a treasure of Islamic knowledge that explains the principles of Islamic law. These rules are a means of responding to every development and solving problems in the midst of people's lives, especially Muslims. The developments in question include the dissemination of information, human resources, technology, ideology or religion, and bureaucracy. With this, the author is very interested in conducting research. This research uses a descriptive qualitative approach where the data is in the form of theories, concepts and ideas. The descriptive qualitative approach aims to reveal or describe the data obtained. The next step taken by researchers is data processing and analysis, which is an effort made by working with data, organizing data, and sorting it so that a relationship is found between one another and providing an interpretation that can be accepted logically. Meanwhile the results of this research are; can improve the quality of human faith, avoid taqlid, avoid committing sins, and can become a person who is always learning. Apart from the benefits above, ushul fiqh can also respond to every change and progress that occurs, and can even solve every problem that occurs in society in various aspects of life. For example, issues of multiculturalism and religious pluralism, globalization and technology, modern medicine, and Islamic economics. Key words: ushul fiqh; society; ideology; religion; human resources